1992
DOI: 10.1002/ddr.430260203
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic profile and side‐effect liability of haloperidol, risperidone, and ocaperidone as predicted from their differential interaction with amphetamine in rats

Abstract: Megens, A.A.H.P., C.J.E. Niemegeers, and F.H.L. Awouters: Antipsychotic profile and side-effect liability of haloperidol, risperidone, and ocaperidone as predicted from their differential interaction with amphetamine in rats. Drug Dev. Res. 26:129-145, 1992. Motor activity effects of haloperidol, risperidone, and ocaperidone were studied in rats challenged with amphetamine. At a low dose of amphetamine, the compounds were about equipotent in reducing amphetamine-induced hyperactivity to normal values (lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Thus, inasmuch as risperidone interacts at 5-HT 1A sites only at concentrations ~100-fold higher than at D 2 receptors (Newman-Tancredi et al 1998), actions at the former are unlikely to be of importance to its antipsychotic profile. A similar situation holds for the structurally related ocaperidone (Megens et al 1992), which stimulated MAPK phosphorylation in the present study. Thus, ocaperidone only partially and weakly (1 µmol/l) attenuated the inhibitory influence of 5-HT on forskolinstimulated AC in HeLa cells expressing h5-HT 1A receptors (Pauwels et al 1993) and only modestly enhanced [ 35 S]GTPγS binding at 5-HT 1A sites expressed in CHO cells, even at high concentrations relative to those blocking D 2 receptors (Newman-Tancredi et al 1998).…”
Section: Phosphorylation Of Mapk By Other Antipsychoticssupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, inasmuch as risperidone interacts at 5-HT 1A sites only at concentrations ~100-fold higher than at D 2 receptors (Newman-Tancredi et al 1998), actions at the former are unlikely to be of importance to its antipsychotic profile. A similar situation holds for the structurally related ocaperidone (Megens et al 1992), which stimulated MAPK phosphorylation in the present study. Thus, ocaperidone only partially and weakly (1 µmol/l) attenuated the inhibitory influence of 5-HT on forskolinstimulated AC in HeLa cells expressing h5-HT 1A receptors (Pauwels et al 1993) and only modestly enhanced [ 35 S]GTPγS binding at 5-HT 1A sites expressed in CHO cells, even at high concentrations relative to those blocking D 2 receptors (Newman-Tancredi et al 1998).…”
Section: Phosphorylation Of Mapk By Other Antipsychoticssupporting
confidence: 71%
“…Thus, a possible role of 5-HT 1A receptors in the "atypical" antipsychotic profile of quetiapine would justify evaluation. While risperidone (Megens et al 1992;Grant and Fitton 1994;Bondolfi et al 1998) failed to stimulate [ 35 S]GTPγS binding (Newman-Tancredi et al 1998), it weakly (21%) enhanced MAPK phosphorylation. This observation provides a parallel to a recent report that WAY100,635 attenuates its influence on frontocortical DA release in rats .…”
Section: Phosphorylation Of Mapk By Other Antipsychoticsmentioning
confidence: 88%
“…The slight selectivity is likely obtained by additional a 1 -adrenoceptor and 5-HT 2 receptor blockade. It could be expected that the high in vitro and ex vivo muscarinic affinity of olanzapine would further enhance selectivity (Bymaster et al 1996a,b), but the in vivo antimuscarinic activity is rather weak in our hands (Figure 1).As mentioned in the ex vivo binding section, it has been shown that risperidone has a more shallow doseresponse curve at DA 0 2 receptors than do other APDs (Megens et al 1992;Schotte et al 1996a). This has been followed up in behavioral experiments showing that the AMPH interaction with risperidone occurs over a wider dose range than observed with classic APDs (Megens et al 1992).…”
mentioning
confidence: 65%
“…This has been followed up in behavioral experiments showing that the AMPH interaction with risperidone occurs over a wider dose range than observed with classic APDs (Megens et al 1992). The impact of this result for evaluation of limbic selectivity is not clear.…”
Section: No 2 Do Novel Antipsychotics Have Similar Pharmacologicalmentioning
confidence: 99%